Respuesta :

Answer:

(2x + 1) (x + 4) hope it helps

Answer:

1.) x = -4                                                     OR

2.) x = -1/2 = -0.500

Step-by-step explanation:

4.2     Solving   2x2+9x+4 = 0 by Completing The Square .

Divide both sides of the equation by  2  to have 1 as the coefficient of the first term :

  x2+(9/2)x+2 = 0

Subtract  2  from both side of the equation :

  x2+(9/2)x = -2

Now the clever bit: Take the coefficient of  x , which is  9/2 , divide by two, giving  9/4 , and finally square it giving  81/16  

Add  81/16  to both sides of the equation :

 On the right hand side we have :

  -2  +  81/16    or,  (-2/1)+(81/16)  

 The common denominator of the two fractions is  16   Adding  (-32/16)+(81/16)  gives  49/16  

 So adding to both sides we finally get :

  x2+(9/2)x+(81/16) = 49/16

Adding  81/16  has completed the left hand side into a perfect square :

  x2+(9/2)x+(81/16)  =

  (x+(9/4)) • (x+(9/4))  =

 (x+(9/4))2  

Things which are equal to the same thing are also equal to one another. Since

  x2+(9/2)x+(81/16) = 49/16 and

  x2+(9/2)x+(81/16) = (x+(9/4))2  

then, according to the law of transitivity,

  (x+(9/4))2 = 49/16

We'll refer to this Equation as  Eq. #4.2.1  

The Square Root Principle says that When two things are equal, their square roots are equal.

Note that the square root of

  (x+(9/4))2   is

  (x+(9/4))2/2 =

 (x+(9/4))1 =

  x+(9/4)

Now, applying the Square Root Principle to  Eq. #4.2.1  we get:

  x+(9/4) = √ 49/16  

Subtract  9/4  from both sides to obtain:

  x = -9/4 + √ 49/16  

Since a square root has two values, one positive and the other negative

  x2 + (9/2)x + 2 = 0

  has two solutions:

 x = -9/4 + √ 49/16  

  or

 x = -9/4 - √ 49/16  

Note that  √ 49/16 can be written as

 √ 49  / √ 16   which is 7 / 4  

Solve Quadratic Equation using the Quadratic Formula

4.3     Solving    2x2+9x+4 = 0 by the Quadratic Formula .

According to the Quadratic Formula,  x  , the solution for   Ax2+Bx+C  = 0  , where  A, B  and  C  are numbers, often called coefficients, is given by :

                                     

           - B  ±  √ B2-4AC

 x =   ————————

                     2A  

 In our case,  A   =     2

                     B   =    9

                     C   =   4  

Accordingly,  B2  -  4AC   =

                    81 - 32 =

                    49

Applying the quadratic formula :

              -9 ± √ 49  

  x  =    —————

                   4

Can  √ 49 be simplified ?

Yes!   The prime factorization of  49   is

  7•7  

To be able to remove something from under the radical, there have to be  2  instances of it (because we are taking a square i.e. second root).

√ 49   =  √ 7•7   =

               ±  7 • √ 1   =

               ±  7  

So now we are looking at:

          x  =  ( -9 ± 7) / 4

Two real solutions:

x =(-9+√49)/4=(-9+7)/4= -0.500  

or:

x =(-9-√49)/4=(-9-7)/4= -4.000  

Two solutions were found :

x = -4

x = -1/2 = -0.500

Processing ends successfully

ACCESS MORE